In Vitro Activity of Oral Cephalosporins (Cefprozil and Cefixime) Against Ciprofloxacin-Resistant Enterobacteriaceae from Community-Acquired Urinary-Tract Infections. Issue 4 (December 2015) - Pistiki, Aikaterini; Tsaganos, Thomas; Galani, Irene; Giamarellos-Bourboulis, Evangelos
Abstract Introduction The global emergence of pathogens of urinary-tract infections resistant to ciprofloxacin or producing extended-spectrum β-lactamases (ESBL) led us to investigate the activity of older antimicrobials such as cefprozil and cefixime against a recent broad collection of urine enterobacteria from 2012 and 2013. Methods Minimum inhibitory concentrations and minimum bactericidal concentrations of cefprozil, cefixime and ciprofloxacin were determined against 293Escherichia coli (40 ESBL producers), 54Klebsiella pneumoniae (10 ESBL producers) and 53Proteus mirabilis isolates. Results Cefprozil was more active than ciprofloxacin against non-ESBL-producingE. coli (93.7% vs 80.2%, p  < 0.0001); this was not the case for cefixime (85.7% vs 80.2%, p : 0.125). Overall, cefprozil and cefixime inhibited 80–90% of ciprofloxacin-resistant isolates of all studied species. However, they were active against less than 20% of ESBL-producing isolates. Conclusion Results suggest that cefprozil and cefixime remain a good therapeutic alternative against urine enterobacteria particularly in case of ciprofloxacin-resistant pathogens. Their activity against ESBL-producing pathogens is limited.